2022
DOI: 10.1039/d1qi01508g
|View full text |Cite
|
Sign up to set email alerts
|

Nominally stoichiometric Na3(WxSixSb1−2x)S4 as a superionic solid electrolyte

Abstract: Na3MX4 (M = P, Sb and X = S, Se) and its doped analogues are considered as a promising material in room-temperature (RT) Na+-conducting solid electrolytes. Herein, we first report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…By co-doping with two cations (W, Si), Suyeon Han synthesized Na 3 W 0.2 Si 0.2 Sb 0.6 S 4 in 2021, and an ionic conductivity of 13.2 mS cm −1 was achieved at room temperature. 10 However, whether the same effect will be achieved through the co-doping of anions and cations remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…By co-doping with two cations (W, Si), Suyeon Han synthesized Na 3 W 0.2 Si 0.2 Sb 0.6 S 4 in 2021, and an ionic conductivity of 13.2 mS cm −1 was achieved at room temperature. 10 However, whether the same effect will be achieved through the co-doping of anions and cations remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…hugely relies upon the development of affordable, easily scalable, and environmentally benign functional materials possessing superior ionic conductivities. [1][2][3][4] Since essential prerequisites for the ionic conductive properties are established at the level of electronic and crystal structures, the design of ion conductors is primarily focused on structural types comprising a percolating system of energetically available voids and cavities, such as β-Al 2 O 3 , [5][6][7][8][9] NASICONs, [10][11][12][13][14][15][16] boranes, 17,18 silicates, [19][20][21] chalcogenides, [22][23][24][25][26] and molybdates. 27,28 In the last decade, the KTiOPO 4 (KTP) structured materials with the AMTO 4 X general formula (Aalkali metal; Mp-or d-metal; T -P, S; X -O, F) emerged as promising electrochemically active materials for diverse metal-ion battery technologies due to their unique structure offering boosted redox potentials and high alkali-ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The low elastic modulus of so sulde lattices enables cell fabrication via an industrially adaptable route (e.g., cold-press). 18 Among these, the most noteworthy examples are found in the Na 4 M(IV) S 4 -Na 3 M(V)S 4 -Na 2 M(VI)S 4 ternary system, [19][20][21][22][23][24][25][26][27][28][29][30][31] wherein M(IV) includes Si 4+ , Ge 4+ , and Sn 4+ ; M(V) represents P 5+ , As 5+ , and Sb 5+ ; and, M(IV) denotes W 6+ and Mo 6+ . For example, Hayashi et al reported an unprecedented s ion of 32 mS cm −1 (sintered pellet) at RT for Na 2.88 Sb 0.88 W 0.12 S 4 , 32 wherein defect-mediated Na + migration contributed to superionic conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Cold-pressed Na 2.88 (W 0.22 Si 0.10 Sb 0.68 )S 4 revealed the highest s ion of 20.2 mS cm −1 and the lowest activation barrier of 0.14 eV within a pseudo-ternary compositional system. 31,35 The electrochemical stability of these SSEs, however, is known to be quite narrow and phase stability is exhibited only within voltage windows of 1.16-2.49 V (Na 3 PS 4 ) and 1.54-2.35 V (Na 3 SbS 4 ). 36,37 Na 3 M(II)M(III)Q 4 (M(II) = Mn 2+ , Fe 2+ , Co 2+ , M(III) = Ga 3+ , In 3+ , and Q = S 2− , Se 2− ) is a relatively new class of Na + -conducting SSEs.…”
Section: Introductionmentioning
confidence: 99%